“Delirium” en el paciente oncológico - Rivera, Fernando; López, Carlos; Vega, Mª Eugenia; Juan, Ana de; García, Almudena; Martínez, Eva; Sanz, Jaime (Psicooncología, 2004)
Delirium is a functional disorder of the central nervous system, very common among oncological patients, consequence of the presence in the organism of “false neurotransmitters” that could be exogenous or endogenous and give place to alterations inside several aspects (cognitive, perceptive, behavior, attention). The restoration of the symptoms is acute and the course is fluctuating along the day. In an important percentage of the cases the situation is reversible. Nevertheless, in other occasions it is an indicator of a situation premortem of the patient (“terminal agitation”). Most of cases etiology is multifactorial and there can be implied both, the proper tumor and the treatments administered to fight it or to solve the symptoms that this one causes (chemotherapy, opioids, steroids). The managing of this entity implies several questions of psychological area (information to the family), of environmental hygiene (skills of reorientation) and pharmacologist (control the symptoms with neuroleptics, benzodiacepines). Nevertheless, the most important point is to eliminate the ethiologic factor, in case of this one exists.